Analisis Pindah Panas Konduksi dan Konveksi pada Heat Exchanger Evaporator Efek Ganda pada Pengolahan Nira Tebu - Khoirul Anam As Syukri; Dony Perdana; Moch. Izza Maulana Sulthon; Sumardi Hadi Sumarlan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Heat transfer occurs due to differences in temperature contained in an object. In this study only discussed about heat transfer by conduction, and by convection (inside and outside the tube). The purpose of this study was to determine the value of conduction and convection heat transfer in the heat exchanger of the sugarcane juice evaporation process using a dual effect evaporator and its effect on the rate of evaporation. The method used through observation and experimentation on the heat exchanger contained in the second tube evaporator. The materials used were 50 liters of sugar cane juice in the 1 effect tube and 26 liters of the effect tube 2. Experiments and data collection in the form of temperature, pressure, and volume were carried out 3 times. Each repeat process was carried out at 5.2 hours under vacuum. The temperature and pressure data were recorded every 10 minutes. In addition, the plate thickness, plate type, material contact surface area and characteristics of the processed material were determined. Furthermore, the data is substituted in several heat transfer equations to get the value. Based on the results of the study, the overall heat transfer coefficient value of the convection heat transfer is 35.98 w / m2K. Meanwhile, the total heat transfer from convection and conduction to the heat exchanger is 4656.6 watts. This heat transfer value can cause the evaporation rate of sugarcane juice to effect 2 of 1.03 liters / hour.